Numerical modeling of electrical parameters of LiFePO4 batteries - Buryk, Mykola; Lobodzinsky, Vadim; Buryk, Ivan; Lisovyi, Oleksandr (Technology audit and production reserves, 2024)
The object of research is the physical processes of electric energy storage in Li-ion batteries. The problem being solved in the work is related to the lack of reliable mathematical models of storage batteries, which leads to the appearance of undesirable effects or emergency situations when changing operating modes. In the course of the work, Li-ion battery models based on electrochemical theory and electrical circuits were considered. The six most common equivalent battery replacement schemes are presented. The advantages and disadvantages of the considered substitution schemes are given. The dual-polarization mathematical model was found to most accurately describe the performance of the battery at the end of the discharge and charge cycles compared to the first-order Thevenin model, the RC model, and the active resistance battery model. The physical processes in the storage battery during pulse discharge, which is the main part of electrical energy storage systems based on electrochemical technology, were studied. Mathematical modeling was carried out in the Matlab software package using the Simulink application program package. The dependence of the parameters of the equivalent lithium-ion battery replacement scheme according to the second-order Thevenin model on the ambient temperature and state of charge is considered. It was established that the value of EMF E depends more on the change in SOC than on temperature. In turn, the active resistance ROM shows a greater dependence on temperature than on the change in SOC. At high temperatures, the resistance value decreases. The parameters R1 and C1 characterizing the electrochemical polarization vary in the range from 10 to 75 % SOC. The parameters R2 and C2, which depend on the concentration polarization, vary in the intervals from 0 to 25 % SOC and 75 to 100 % SOC. The recommendations for choosing a Li-ion battery model developed in the work can be used in practice. The established dependencies will help to better design electrical energy storage systems based on electrochemical technology.